Spectrum and clinical profile of disorders of sex development: A 10 year experience at a tertiary care center - Nida Aslam; Sommayya Aftab; Bushra Naseer Khan; Noor-e-Hira (Pakistan Journal of Medical Sciences, 2026)
Background & Objective: Disorders of Sex Development is a group of congenital conditions characterized by atypical development of chromosomal, gonadal, or anatomical sex. These conditions present diverse clinical challenges and require individualized, multidisciplinary management throughout life. This study aimed to determine the clinical spectrum of children and adolescents with Disorders of Sex Development (DSD) at a tertiary care center over the last decade. Methodology: In this retrospective observational study, 815 children and adolescents (0–18 years) diagnosed with Disorders of Sex Development (DSD) were evaluated at the Department of Pediatrics Endocrinology and Diabetes, University of Child Health Sciences, The Children’s Hospital, Lahore from January 2015 to December 2024. Data regarding demographic characteristics, clinical presentation, karyotype, and final diagnosis were collected and analyzed. Statistical analysis was performed to assess the association between karyotype and subtype distribution, with significance set at p < 0.05. Results: The mean age of presentation was 7.5 ± 5 years, with 62% raised as male and 38% as female. The most common presentation was microphallus (41%), followed by ambiguous genitalia (21.6%) and delayed puberty/primary amenorrhea (20%). Based on karyotype, 46,XY DSD was most common (60.7%), predominantly due to androgen insensitivity and 5α-reductase deficiency (82.4%). 46,XX DSD accounted for 33.4%, mainly congenital adrenal hyperplasia (91.6%), while sex chromosome DSD comprised 6.6%, with Turner Syndrome variants being the most frequent subtype. A statistically significant association was observed between karyotype and subtype distribution (χ² = 167.42, p < 0.0001). Conclusion: DSD presents a broad range of clinical challenges underscoring the need for early accurate diagnosis and appropriate gender assignment. A multidisciplinary approach, improved diagnostic tools, and better education are essential for achieving optimal patient outcomes and reducing the long-term psychological impact of DSD.